Impaired muscle capacity of the hip and knee in individuals with isolated patellofemoral osteoarthritis: a cross-sectional study - Cristiano Carvalho; Fábio Viadanna Serrão; Letícia Mancini; Paula Regina Mendes da Silva Serrão (SAGE Publishing, 2021)
Aims: The aims of this study were to compare the capacity of the knee and hip muscles between individuals with and without isolated patellofemoral osteoarthritis (PFOA) and to evaluate the impact of PFOA on pain, stiffness, and physical function. Methods: This cross-sectional study evaluated muscle capacity of the hip and knee using an isokinetic dynamometer. The isokinetic variables used in the statistical analysis were peak torque, total work, and average power. Pain, stiffness, and physical function were assessed using questionnaires. Results: A total of 26 individuals participated in the study (13 with PFOA and 13 controls). The PFOA group exhibited lower peak torque, total work, and average power for knee extension and flexion in the concentric mode ( p  ⩽ 0.01) as well as lower peak torque and total work for knee extension ( p  ⩽ 0.005) and lower total work for knee flexion ( p  = 0.05) in the eccentric mode. The PFOA group exhibited lower peak torque of the extensor, abductor, adductor, and internal rotator muscles of the hip ( p  ⩽ 0.05), less total work of the abductor and adductor muscles ( p  ⩽ 0.04), and lower average power of eccentric adduction of the hip ( p  = 0.01) compared with the healthy controls. Compared with the control group, the PFOA group had a higher level of pain, stiffness, and compromised physical functioning self-reported ( p  ⩽ 0.005). Conclusion: Participants with PFOA exhibited impairments regarding muscle capacity of the hip and knee, higher level of pain and stiffness as well as compromised physical functioning in comparison with healthy controls.